(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to determine and analyze the ability of Primagraha University students in the 5th semester of Mathematics Study Program in proving mathematically problems in algebraic structure material. This study uses a qualitative research type of case study. The case study itself is a method of knowing and understanding someone using inclusive and comprehensive or comprehensive practices. Through the practice carried out, researchers will collect individuals who are used as research subjects. In-depth information digging will be carried out by researchers for a detailed understanding. In this study, it included students who lacked an understanding of algebraic structure material. The results of the initial observations showed that students who had difficulty understanding algebraic structure material tended to not be confident in asking for repetition of material from the lecturer when they did not understand, were not comfortable with the learning model provided and did not want to discuss with their friends. The research results show that; 1) students who are lacking in understanding algebraic structure material need a learning model that is able to make students comfortable in learning, 2) students need regular discussion rooms when studying algebraic structure material and 3) students need a continuous offline learning pattern for algebraic structure material.